KOLABORASI ORANG TUA DAN GURU DALAM MEMBIMBING KEINGINTAHUAN AGAMA ANAK GENERASI ALPHA - Azima Wahidatu Wildana; Itsna Rusydiana (Al-ATHFAL: Jurnal Pendidikan Anak, 2026)
The emergence of Generation Alpha, who grow up within a highly digitalized environment, has significantly transformed children’s religious curiosity. Religious teachings are no longer accepted merely as dogma; instead, children increasingly raise reflective and existential questions that demand logical and contextual explanations. This study aims to examine the forms of religious curiosity among Generation Alpha children and to analyze the importance of collaboration between parents and teachers in guiding this process. Employing a qualitative phenomenological approach, data were collected through in-depth interviews and participatory observation involving parents and Islamic education teachers. The findings reveal that children’s religious curiosity can be categorized into ontological, epistemological, and axiological questions. The study also demonstrates that a synergistic-dialogical collaboration between parents and teachers is essential to ensure consistency in religious understanding. Digital media function as supportive tools for pedagogical communication and coordination. Furthermore, a constructivist approach proves effective in facilitating dialogical, rational, and moderate religious learning. This research underscores that effective Islamic religious education for Generation Alpha requires sustained cooperation between family and school environments to foster meaningful, reflective, and well-integrated religious understanding.